2021
DOI: 10.3390/biom11081110
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1, Visfatin and IL-27 Serum Levels of Type 1 Diabetic Females in Relation to Cardiovascular Parameters and Autoimmune Thyroid Disease

Abstract: The loss of cardioprotection observed in premenopausal, diabetic women may result from the interplay between epigenetic, metabolic, and immunological factors. The aim of this study was to evaluate the concentration of sirtuin 1, visfatin, and IL-27 in relation to cardiovascular parameters and Hashimoto’s disease (HD) in young, asymptomatic women with type 1 diabetes mellitus (T1DM). Thyroid ultrasound, carotid intima-media thickness (cIMT) measurement, electrocardiography, and echocardiography were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Thyroid autoimmunity is possibly associated with activation of the pathways that promote atherosclerosis, which may contribute to the loss of vasoprotection in women, explaining why they are at higher cardiovascular risk. Own elaboration based on the data obtained in the study and [5,6,8,21,22,29,31,38,41]. Th -T helper cell; HT -Hashimoto's thyroiditis; aTPO -anti-thyroid peroxidase antibody; fT3 -free triiodothyronine…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid autoimmunity is possibly associated with activation of the pathways that promote atherosclerosis, which may contribute to the loss of vasoprotection in women, explaining why they are at higher cardiovascular risk. Own elaboration based on the data obtained in the study and [5,6,8,21,22,29,31,38,41]. Th -T helper cell; HT -Hashimoto's thyroiditis; aTPO -anti-thyroid peroxidase antibody; fT3 -free triiodothyronine…”
Section: Discussionmentioning
confidence: 99%
“…What is important, these factors associated with autoimmunity are also important in regulating the inflammatory processes that underlie CV complication [40]. Interestingly, epigenetic factors may mediate the link between autoimmunity, adipose tissue, and the atherosclerotic plaque formation [41], but the exact mechanism of these relationships remains unclear and requires further study. Figure 2 shows the possible mechanisms involved in the association between factors related to thyroid autoimmunity and atherosclerosis in women.…”
Section: Original Papermentioning
confidence: 99%
“…The possible mechanisms associated with this relationship are the activation of the inflammatory process and oxidative stress connected with thyroid autoimmunity, which may have a systemic effect [34][35][36]. Indeed, it has recently been shown that early myocardial dysfunction may be related to sirtuin 1 and interleukin 27, the serum concentrations of which were higher in women with T1DM and HT than in women with T1DM alone and correlated significantly with several echocardiographic parameters [37]. This is a new insight into the development of HF in women with T1DM and needs to be verified in further research.…”
Section: Original Papermentioning
confidence: 99%
“…There have been preclinical and clinical studies indicating the significance of SIRT1 in the pathogenesis of Ads, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), inflammatory bowel disease (IBD), multiple sclerosis (MS), etc. In women Hashimoto's disease patients with type 1 diabetes mellitus, SIRT1 contributed to the pathogenesis of early cardiac dysfunction (10). Agathe et al performed microarray experiments to identify SIRT1 as a relevant gene candidate associated with pathological angiogenesis in autoimmune arthritis mice (11).…”
Section: Introductionmentioning
confidence: 99%